PENERAPAN KEBIJAKAN PENATAAN DAN SISTEM PEMUNGUTAN PAJAK REKLAME SEBAGAI SARANA PENUNJANG EFEKTIVITAS - Darmanto, Dian Wulansari; Mildawati, Titik (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to find out the policy of structuring and collecting of advertisement tax in Surabaya city, the data is the primary data. The result of the research analysis shows that the potency of advertisement tax in Surabaya city is considered to be great considering the trading and business which is getting improved. Local Department of Revenue and Fiscal Management (DPPKD) of Surabaya, as the management of local financial management in carrying their tasks and functions is influenced by the environmental factor, both internal and external, and some barriers of tax collection both passive and active resistance. It has been found from the result of analysis taxpayers (WP) do not comply to pay the tax, it can be seen from many advertisements which are delinquent in paying tax on the research location. Based on the result of the research it can concluded that there are many taxpayers (WP) who do not comply to pay the tax, it can be seen from many advertisement which delinquent in paying tax on the research location, the socialization which has been done by Local Department of Revenue and Fiscal Management (DPPKD) of Surabaya is held once a year only, this socialization only discusses about the local own source revenue (PAD) which has been obtained on the previous years, so it is considered to be insufficient in providing information about advertisement tax and many taxpayers (WP) who do not attend to the event, therefore there are many taxpayers (WP) who do not know the information about the collection of Advertisement Tax, and the effectiveness level to the potency of the realization of the revenue of advertisement tax has not optimal yet, since it is influenced by some constraint factors such as Tax Avoidance (paying tax in credit), Tax Evasion (paying the advertisement tax under the real potency).Keywords: Advertisement Tax, Surabaya City and Effectiveness